The spatial dimension in FDI spillovers: evidence at the regional level from Portugal - Crespo, N.; Proença, I.; Fontoura, M. P. (Regional and Sectoral Economic Studies, 2012)
There are theoretical reasons to expect that benefits to domestic firms from foreign direct investment would be confined to the area where the multinational firm is located and that the benefits depend on the development level of the host region. However, there is a scarcity of empirical studies on FDI’s indirect effects at the regional level, particularly with regard to inter-industry spillovers. This paper is an empirical contribution to this literature with data for Portugal. Both intra-industry and inter-industry FDI spillovers are considered. The concept of region adopted comprises the county in which the domestic firm is located, together with all of the directly neighbouring counties. Equations are estimated using the System GMM, with robust estimation of covariance matrices. Data confirms the relevance of both the geographical proximity and the development level of the region to this phenomenon. Furthermore, FDI spillovers are more evident at the inter-industry level. These results raise important implications for economic policy.